Labor Disputes In Enforcing Justice In The Era Of The Covid-19 Pandemic - Bryllian Erix Darmawan; Elsa Putri Supriyanto; Meliana Murti Prakastiwi; Salwa Billa Mirza Ridwan; Laila Alfida; Boris Gabe Tobing (Proceeding International Conference Restructuring and Transforming Law, 2022)
Various kinds of impacts have been received on the economic sector caused by the COVID-19 pandemic in Indonesia. First, many companies suffer heavy losses and decide to do massive layoffs of their jobs. This can be seen from the research data that there are 1.5 million workers working in companies. This study uses the method of literature review and data search techniques using documents. In addition, the omnibus law passed suddenly made major changes to workers' rights and environmental regulations. Unions say at least 2 million workers have taken to the streets to protest, while Reuters and the Associated Press reported that thousands of workers and students attended. The student union said they would join forces with the workers to express their aspirations in the form of upholding justice. The results showed that the workers rejected the entire contents of the omnibus law which was very detrimental to workers